2005
DOI: 10.2337/diabetes.54.8.2404
|View full text |Cite
|
Sign up to set email alerts
|

Role of Insulin Secretion and Sensitivity in the Evolution of Type 2 Diabetes in the Diabetes Prevention Program

Abstract: Insulin resistance and ␤-cell dysfunction, two factors central to the pathogenesis of type 2 diabetes, were studied in relation to the development of diabetes in a group of participants with impaired glucose tolerance in the Diabetes Prevention Program (DPP) at baseline and after specific interventions designed to prevent diabetes. Participants were randomly assigned to placebo (n ‫؍‬ 1,082), metformin (850 mg twice a day) (n ‫؍‬ 1,073), or intensive lifestyle intervention (n ‫؍‬ 1,079). The diabetes hazard ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
143
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(157 citation statements)
references
References 51 publications
7
143
1
1
Order By: Relevance
“…This improvement in insulin sensitivity was associated with reduction of the risk of the development of diabetes overall and in each treatment arm (16). This is concordant with other diabetes prevention randomized controlled trials showing that improvement in insulin sensitivity induced by lifestyle intervention is a strong predictor of risk reduction in individuals with diabetes (17).…”
Section: Discussionmentioning
confidence: 99%
“…This improvement in insulin sensitivity was associated with reduction of the risk of the development of diabetes overall and in each treatment arm (16). This is concordant with other diabetes prevention randomized controlled trials showing that improvement in insulin sensitivity induced by lifestyle intervention is a strong predictor of risk reduction in individuals with diabetes (17).…”
Section: Discussionmentioning
confidence: 99%
“…We could not find the same prediction with β-cell functions represented by HOMA-BCF and the insulinogenic indices. Although it has been well accepted that the interplay between insulin resistance and decrease in β-cell capacity predates the occurrence of frank DM [35,36,37,38,39,40,41,42], Tabák et al [43] have recently demonstrated that β-cell function might not decline until 2 years prior to the occurrence of DM. Their finding also suggests that insulin sensitivity could start to decline as long as 13 years prior to the occurrence of DM while the trajectory of β-cell function could follow a rise between 3 and 4 years and decline 2 years prior to DM [43].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the association between H. pylori infection and insulin resistance with mixed results 15,16,21,38 but none have reported the association between H. pylori and composite beta-cell function as measured by disposition index-like measure from OGTT, which is a measure of pancreatic beta cell function that captures both insulin secretion and insulin sensitivity 23 . A low disposition index-like measure from OGTT indicates an impaired pancreatic beta cell function and is a validated predictor of diabetes risk 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…A composite beta-cell function (disposition index-like measure from OGTT) was estimated by the product of the corrected insulin response (CIR) and insulin-sensitivity index (ISI), as previously used in the DPP 23 . Corrected insulin response was calculated as follows: (100 × insulin at 30 minutes) ÷ (glucose at 30 minutes × [glucose at 30 minutes – 70 mg/dL]).…”
Section: Methodsmentioning
confidence: 99%